The Comparison Of The Indonesian Ppatk Role With Other Countries Financial Intelligence Unit (FIU) - Nikmah Rosidah (UBL, 2013)
Today the fight against international money laundering activities is increasing, even in many countriesand on a regional basis it has become one of the political agenda that is always discussed. Some of thethings that drive a number of governments to combat money laundering especially is a concern oforganized crime that the results so far untouched by the aplicable laws and regulations, in addition to theinternational pressure on countries that have not implemented anti-money laundering regime completely,as experienced by Indonesia and other countries.